Isometric and dynamic performances of the trunk and associated factors - Malchaire, J B; Masset, D F (Spine (Philadelphia, Pa. 1976), 1995)
Static and dynamic performances of the trunk were measured on an isoinertial device and data were collected regarding the working conditions and the anthropometric and psychosocial characteristics of the workers. To describe the difference in static and dynamic performances of the trunk between workers with and without low back pain and to investigate the anthropometric, personal, and occupational factors associated with these performances. The isometric torque and the parameters of displacement, velocity, and torque during dynamic tests were chosen to describe the isoinertial performances of the trunk. Dynamic characteristics in particular were investigated because it has been suggested in the literature that these discriminate best between workers with and without low back pain. The protocol included a 52-item questionnaire, a clinical examination with a series of anthropometric measurements, and the isometric and dynamic tests (against 25% and 50% of the isometric values) on the isostation. The variables significantly associated with the trunk performances were weight, height, muscularity, sports, and leisure activities as positive factors, and linearity, health problems, and vehicle driving as negative factors. When these covariates were taken into consideration, the significant differences between subjects with and without low back pain were related only to the velocities during dynamic tests, which were reduced by 5.9%. The performances of the trunk are associated mainly with the anthropometric characteristics of the subjects but also with factors such as lumbar status, health, working conditions, and leisure activities.